KONTRASTIF INDONESIA-ARAB: PENGUNGKAPAN MAKNA KONJUGASI VERBA BAHASA ARAB DALAM BAHASA INDONESIA - Yerry Mijianti; Mohamad Afrizal (CMES (Center of Middle Eastern Studies), 2015)
As an inflection language, the verb in Arabic language (VAB) has many meaning of inflection which is called the conjugation. This research will try to explore the meaning of conjugation and all aspects inside the verb in Arabic Language (VAB). This research is very important because in Arabic language, based on the morphology, Arabic language was classified as an inflection language. In the other side, Bahasa Indonesia was categorized as agglutinative language. Thus, it was need the contrastive study toward the conjugation meanings of VAB and how to reveal the conjugation meanings of VAB and how to reveal it in Indonesian language. The method used in this research such as: the data collection, the data analysis, and the report of research’s data analysis results. The method of collecting the data was occured by observing the conjugation of verbs and also by ensuring the meanings from the books of Arabic gramatical.  The analysis method that has been used in this research is distributional method combined by the technique of opposition, the technique of directly substances divided, the technique of ellipsis and the technique of change; and also the method of translational equal, such as the technique of classifying the certain substance and also the technique of connecting and comparing. The report of data analysis was delivered by the formal and informal type of reporting data. The result of this research is concluded that the VAB is not including all of the meaning of conjugation inflection.